Cellular Automata Describing Non-equilibrium Fluids with Non-mixing Substances - Ramos, Carlos (2022)
A family of cellular automata arising from perturbations of a basic cellular automata rule, represented by 3E6IGS58S, in base 32, is studied. These rules can be seen as modeling idealized fluids in non-equilibrium, subject to interaction on distinct phases. Using adaptive techniques such as assembly and singular perturbation of cellular automata, we present several simulations showing the increase of complexity in the perturbed systems behavior, in particular, showing the increasing number of distinct spatial-temporal patterns exhibited.